Joseph Conrad's Heart of darkness & The secret sharer - Conrad, Joseph; Bloom, Harold (New Delhi : New Delhi, 2007)
A guide to reading "Heart of Darkness" and "The Secret Sharer" with a critical and appreciative mind. Includes background on the author's life and times, sample tests, term paper suggestions, and a reading list.
Includes bibliography.
Keywords: English literature -- History and criticism